Trade and Global Market 2018
DOI: 10.5772/intechopen.74406
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Exchange Rate Volatility on Macroeconomic and Financial Variables: Empirical Evidence from PVAR Modeling

Abstract: In this study, Panel Vector Autoregression (PVAR) models are used to determine the impacts of exchange rate volatility on industrial production growth rate, consumer price inflation, short-term interest rates and stock returns for 10 OECD countries. The variance decompositions (VDCs) found that exchange rate volatility can be a secondary factor for the variations in immediate interest rates, implying that Uncovered Interest Rate Parity (UIP) condition should be analyzed by the inclusion of other macroeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The result by Janus and Riera-Crichton (2015) on some OECD countries revealed an inverse correlation between exchange rate changes and the GDP. In another study, a positive association was shown in the results of the Panel Vector Autoregression models on the interplay of exchange rate volatility, inflation rate and returns on stocks for 10 OECD countries by Ozcelebi (2018). The Impulse Response outcome of the VAR of the study further revealed that volatility of the exchange rate could impact positively on economic activities via a fall in interest rate.…”
Section: Review Of Related Literaturementioning
confidence: 83%
See 1 more Smart Citation
“…The result by Janus and Riera-Crichton (2015) on some OECD countries revealed an inverse correlation between exchange rate changes and the GDP. In another study, a positive association was shown in the results of the Panel Vector Autoregression models on the interplay of exchange rate volatility, inflation rate and returns on stocks for 10 OECD countries by Ozcelebi (2018). The Impulse Response outcome of the VAR of the study further revealed that volatility of the exchange rate could impact positively on economic activities via a fall in interest rate.…”
Section: Review Of Related Literaturementioning
confidence: 83%
“…Opinions vary about the association between exchange rate volatility and its effect on macroeconomic performance. While some have argued that exchange rate instability drives economic growth in an economy (Ozcelebi 2018), others have argued that it hampers the growth process (Barguellil et al 2018). Possible reason for the differences in the findings of researchers may have emanated from data usage, methodology, the period of study and country-specific features (Phiri 2018).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Before using the PVAR model for estimation, the optimal lag order of the model shall be determined. Based on the existing PVAR2 program research results [36], AIC, BIC, and hqic statistics are constructed to determine the optimal lag order. Then, referring to the research of relevant scholars [37], the standard of the best lag order is: under the AIC, BIC, and hqic criteria, the minimum value.…”
Section: Lag Order Selectionmentioning
confidence: 99%
“…Trade Balance (Bustaman & Jayanthakumaran, 2007), (Arifin & Mayasya, 2018), (Wulansari, 2017); Inflation (Keefe, 2020), (Okechukwu et al, 2019), (Ozcelebi, 2018); Interest Rates (Okechukwu et al, 2019), (Kasman et al, 2011) and (Wulansari, 2017).…”
Section: A Introductionmentioning
confidence: 99%